Development of KASP markers assisted with soybean drought tolerance in the germination stage based on GWAS - Jia, Qianru; Zhou, Miaomiao; Xiong, Yawen; Wang, Junyan; Xu, Donghe; Zhang, Hongmei; Liu, Xiaoqing; Zhang, Wei; Wang, Qiong; Sun, Xin; Chen, Huatao (Frontiers in Plant Science, 2024)
Soybean [Glycine max(L.)Merr.] is a leading oil-bearing crop and cultivated globally over a vast scale. The agricultural landscape in China faces a formidable challenge with drought significantly impacting soybean production. In this study, we treated a natural population of 264 Chinese soybean accessions using 15% PEG-6000 and used GR, GE, GI, RGR, RGE, RGI and ASFV as evaluation index. Using the ASFV, we screened 17 strong drought-tolerant soybean germplasm in the germination stage. Leveraging 2,597,425 high-density SNP markers, we conducted Genome-Wide Association Studies (GWAS) and identified 92 SNPs and 9 candidate genes significantly associated with drought tolerance. Furthermore, we developed two KASP markers for S14_5147797 and S18_53902767, which closely linked to drought tolerance. This research not only enriches the pool of soybean germplasm resources but also establishes a robust foundation for the molecular breeding of drought tolerance soybean varieties.